ANALISIS KEPUASAN MAHASISWA TERHADAP PEMBELAJARAN ONLINE DI ERA PANDEMI COVID-19 - Rostiawati, Iis (Unit Penelitian dan Pengabdian kepada Masyarakat Politeknik TEDC Bandung Jl. Pesantren Km 2 Cibabat Cimahi Utara, Cimahi 40513 Jawa Barat, Indonesia, 2022)
The Covid-19 pandemic that has occurred around the world has affected all aspects of life, including in the world of education. The physical distancing policy issued by the government to suppress the spread of the COVID-19 virus has changed conventional learning activities from face-to-face methods to online learning, including at the higher education level. Understanding and satisfaction of students in online learning is a measure of the effectiveness of teaching and learning activities. This study aims to determine the level of student satisfaction with online learning during the Covid-19 pandemic. The level of student satisfaction with online learning is limited to aspects of learning. This research uses descriptive analysis. The population in this study were active students in the 2020-2021 Academic Year, which is 8528 students. The number of research samples was 2406 students. The results of the study explained that students were satisfied and assessed that the implementation of online learning had gone well. Students do not find it difficult in the learning process that is being undertaken and is supported by e-learning applications that are easily accessible and used. In facing the next semester's lectures, as many as 1651 students agreed to the implementation of offline lectures if conditions permit, while 755 students wanted lectures to continue to be held online.